Role of Calcium Supplementation on Pregnancy Induced Hypertension Outcomes - Ola Hussein Jasim; Waleed Ibraheem Ali; Alaa Moyasser Sadiq (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Pregnancy induced hypertension (PIH), is an important cause of both maternal and perinatalmorbidity and mortality. Low dietary calcium (Ca) intake represents a factor associated with an increasedincidence of hypertensive disease in general and in pregnant population in most low and middle income countries.Ca supplementation has the potential to reduce adverse gestational outcomes of PIH.Aim: To assess the effects of low-dose Ca supplementation on PIH outcomes.Method: A single- blind, randomized controlled trial was conducted in January through March, 2021. A totalnumber of 66 pregnant women with PIH at their 20th week of gestation attended maternal care outpatient inBaghdad Medical City were assigned randomly in two groups those received Ca supplementation 500 mg/day vsnone and follow up both groups till delivery for outcomes.Results: A significant reduction in diastolic blood pressure mean (93.28 mmHg vs. 88.62 mmHg, P= 0.015) andalmost significant reduction in systolic blood pressure mean (149.65 mmHg vs. 142.58 mmHg, P= 0.051) in theparticipants after receiving Ca supplements. Pre eclampcia (10.3% vs. 45.9%, P = 0.002), Low birth weight (6.9%vs. 40.5%, P = 0.002), Pre term delivery (10.3% vs. 43.2%, P=0.003), and admissions to neonatal intensive care unit(10.3% vs. 45.9%, P = 0.002) were significantly lower in the intervention group.Conclusion: Ca supplementation of 500 mg daily started at 20th week of gestation associated with reduction ofmaternal blood pressure, pre-eclampcia, preterm delivery, low birth weight and admission to neonatal intensivecare unit especially in a low dietary Ca intake mothers.